2013
DOI: 10.1155/2013/850473
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Frictional Properties of the C(100)2x1-H Surface

Abstract: Density functional theory-(DFT-) based ab initio calculations were used to investigate the surface-to-surface interaction and frictional behavior of two hydrogenated C(100) dimer surfaces. A monolayer of hydrogen atoms was applied to the fully relaxed C(100)2x1 surface having rows of C=C dimers with a bond length of 1.39Å. The obtained C(100)2x1-H surfaces (C-H bond length 1.15Å) were placed in a large vacuum space and translated toward each other. A cohesive state at a surface separation of 4.32Å that is stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Thus, from the aspects of computational efficiency and accuracy, the slab thickness of the surface‐terminated diamond surface model includes eight carbon atom layers (also eight C atoms in each layer) and two termination layers. In the previous computational studies, eight layers even six layers of carbon atoms were also proved thick enough to represent the diamond surfaces. For the H‐terminated diamond (100) surface, the reconstructed 2 × 1 structure is also the most stable structure, the same as that of the clean surface .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, from the aspects of computational efficiency and accuracy, the slab thickness of the surface‐terminated diamond surface model includes eight carbon atom layers (also eight C atoms in each layer) and two termination layers. In the previous computational studies, eight layers even six layers of carbon atoms were also proved thick enough to represent the diamond surfaces. For the H‐terminated diamond (100) surface, the reconstructed 2 × 1 structure is also the most stable structure, the same as that of the clean surface .…”
Section: Methodsmentioning
confidence: 99%
“…f 1 −f 4 are zero for the vast majority of systems studied with OPLS-AA, 35,36,41 but in this work, some nonzero values are reported. Unlike their hydrogenated counterparts, PFPEs assume conformations that are asymmetric about ether (i.e., C−O) bonds 33,34 and thus phase angles are required to accurately model all dihedrals with central CF n −O bonds. To fit dihedral energy profiles, leastsquares regression was performed using the open-source Multidisciplinary Design Analysis and Optimization (Open-MDAO) framework written in Python 47 to minimize the differences in relative energies between ab initio structures and energies calculated according to eq 2; in some cases, one or more Fourier terms were removed during this process because they were not needed to accurately reproduce the curve.…”
Section: ■ Simulation Methodsmentioning
confidence: 99%
“…42 This observation is consistent with experiments and prior QM calculations, which showed that the C−O bond in perfluorodimethyl ether (CF 3 −O−CF 3 ) is shortened (r 0 ≈ 1.37 Å) compared to dimethyl ether (CH 3 − O−CH 3 ) (r 0 ≈ 1.43 Å). 33,34 Another example is the C F −O−C F angle, whose equilibrium value (θ 0 ) was increased to 121.4°f rom the equilibrium value of 109.5°used to model C H −O−C H angles in hydrogenated ethers. 42 This result is also consistent with experiments and prior QM calculations, which have shown that the C−O−C angle in perfluorodimethyl ether is significantly increased (θ 0 ≈ 120°) compared to dimethyl ether (θ 0 ≈ 112°).…”
Section: ■ Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations